Endothelial Colony Forming Cells (ECFCs) in murine AKI – implications for future cell-based therapies. Issue 1 (December 2017) - Patschan, D.; Schwarze, K.; Tampe, B.; Zeisberg, M.; Patschan, S.; Müller, G.
Abstract Background In recent years, early Endothelial Progenitor Cells (eEPCs) have been proven as effective tool in murine ischemic AKI and in diabetic nephropathy. The mechanisms of eEPC-mediated vasoprotection have been elucidated in detail. Besides producing a diverse range of humoral factors, the cells also act by secreting vasomodulatory microvesicles. Only few data in contrast have been published about the role of so-called Endothelial Colony Forming Cells (ECFCs - late EPCs) in ischemic AKI. We thus aimed to investigate ECFC effects on postischemic kidney function over several weeks. Our special interest focused on endothelial-to-mesenchymal transition (EndoMT), peritubular capillary density (PTCD), endothelial alpha-Tubulin (aT - cytoskeletal integrity), and endothelial p62 (marker of autophagocytic flux). Methods Eight to twelve weeks old maleC57Bl/6 N mice were subjected to bilateral renal pedicle clamping for 35 or 45 min, respectively. Donor-derived syngeneic ECFCs (0.5 × 106 ) were i.v. injected at the end of ischemia. Animals were analyzed 1, 4 and 6 weeks later. Results Cell therapy improved kidney function exclusively at week 1 (35 and 45 min). Ischemia-induced fibrosis was diminished in all experimental groups by ECFCs, while PTCD loss remained unaffected. Significant EndoMT was detected in only two of 6 groups (35 min, week 4 and 45 min, week 6), ECFCs reduced EndoMT only in the latter. Endothelial aT declined under almost all experimental conditions and these effects were further aggravated by ECFCs. p62 was elevated in endothelial cells, more so after 45 than after 35 min of ischemia. Cell therapy did not modulate p62 abundances at any time point. Conclusion A single dose of ECFCs administered shortly post-ischemia is capable to reduce interstitial fibrosis in the mid- to long-term whereas excretory dysfunction is improved only in a transient manner. There are certain differences in renal outcome parameters between eEPCs and ECFC. The latter do not prevent animals from peritubular capillary loss and they also do not further elevate endothelial p62. We conclude that differences between eEPCs and ECFCs result from certain mechanisms by which the cells act around and within vessels. Overall, ECFC treatment was not as efficient as eEPC therapy in preventing mice from ischemia-induced mid- to long-term damage.